Cost of water acquisition from forested watershed - Zulkeflee, Zufarzaana; Mohamad Pauzi, Jinan; Yusoff, Mohd Kamil; Jamil, Nor Rohaizah (Elsevier, 2015)
Estimation of the cost of water acquisition from two watershed, namely Sungai Teranum catchment area and Sungai Sia catchment area in Raub, Pahang, from the overall cost of managing the watershed by the Pahang State Forestry Department was conducted. Field measurements of river flow velocity and cross-sectional area of the rivers were conducted and the average flow rates (m3/s) were determined using the formula Q=VA. It is estimated that the cost of 1 m3 of water generated from the Sungai Teranum catchment with an average water yield of 13868498.29 m3/yr is RM 0.0019 and RM 0.00069 from the Sungai Sia catchment with an average water yield of 113345052.96 m3/yr.